Are we there yet? Localisation as the journey towards locally led prac tice: models, approaches and challenges - Baguios, Arbie; King, Maia; Martins, Alex; Pinnington, Rose (ODI, 2021)
Localisation and locally led international development practice has lo ng been discussed, but has still not been delivered. Systemic barriers have posed challenges, and the term itself is contested. Now, the las t tumultuous 18 months could provide a critical juncture to finally mo ve forward with this crucial agenda. The pandemic has highlighted stru ctural inequalities in the global system, and disrupted ways of workin g in the international development sector. The Black Lives Matter move ment has brought conversations about racism and colonialism to the for e. And the climate crisis has highlighted the need for global action o n humanity’s challenges that remain rooted in local realities. The eme rging analysis in this review aims to set out the key issues in this a genda, building on a wealth of existing knowledge. It aims to span sec tors, highlighting many new and existing models and approaches in the humanitarian, development, philanthropic and private sectors. It revie ws the barriers and challenges to localisation and locally led practic e, with a view to informing a campaign for systemic change to move for ward with this agenda. The review is based on: a rapid review of the l iterature and evidence on localisation and locally led practice; two c onsultations with over 100 total participants, targeted at Global Sout h actors; and analysis of 28 existing models and approaches.